THE INTEGRITY OF SOME PEOPLE, AS WELL AS STATE OFFICIALS, FROM A BIBLICAL PERSPECTIVE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Through this study we will present the scriptural image of some examples of honest people, either in their personal lives or in relation to their peers, the church of their time, as well as state officials, in difficult political situations, personalities who have remained for posterity as models of integrity in their service in the state apparatus where for a period of time they worked. These examples taken for analysis were Deacon Stephen, Joseph, Nehemiah and Job, who did not compromise in any way, remaining models of life and ministry.